A study to assess internet addiction among undergraduate medical students of MMC&RI, Mysore - J., Sushma; Ahmed, Mansoor; A. M., Amrutha (International Journal Of Community Medicine And Public Health, 2018)
Background: Developmental stressors, along with free access to Internet services, may contribute to college student's vulnerability to internet dependence. Research indicates that Internet addiction is often associated with depression, impulse control disorder, and low self-esteem. Medical students are a particularly vulnerable group on account of the time they spend on the internet. The objective of the study was to assess Internet addiction among undergraduate medical students of MMC&RI using Young’s internet addiction test. Methods: A cross sectional observational study was conducted among medical students of MMC&RI during the period from August to November 2015. A total of 236 students were included. Kimberly young’s internet addiction test was used to assess the level of internet addiction. Results: The mean age of the students was 20.6 years (SD 1.97). The mean duration of internet use was 4.4 years (SD 1.64) and the mean duration of internet use per day was 1.96 hours (SD 0.99). The prevalence of severe internet addiction, moderate internet addiction, and mild internet addiction were found to be 0.8%, 19.5% and 58.2% respectively. Conclusions:There is a need to focus on mental health with regard to internet Addiction, as problematic internet use is increasingly being reported and younger Internet users are more at risk of becoming Internet addicts.